2002
DOI: 10.1097/00001888-200205000-00004
|View full text |Cite
|
Sign up to set email alerts
|

One Schoolʼs Strategy to Assess and Improve the Vitality of Its Faculty

Abstract: The authors report how one medical school took an evidence-based, collaborative approach to assessing and improving faculty vitality by building on previous research and including important shareholders (e.g., faculty and administrators). In 1999, the dean and faculty senate asked all full-time faculty (615) at the University of Minnesota Medical School-Twin Cities to complete a survey to (1) identify vitality areas (individual, institutional, or leadership) in which the school was strong and ones that needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 10 publications
3
99
0
1
Order By: Relevance
“…6,7 A network of productive colleagues is among the strongest predictors of research publications, productivity, retention and advancement of academic faculty and of career satisfaction among medical school faculty. [8][9][10][11][12] A survey of academic physician educators indicated that their association with people including mentors and peers was an essential element for career fulfillment. 9 At the organizational level, connections are seen within organizational units that provide the context in which faculty work and train (e.g., labs, centers, divisions, departments).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A network of productive colleagues is among the strongest predictors of research publications, productivity, retention and advancement of academic faculty and of career satisfaction among medical school faculty. [8][9][10][11][12] A survey of academic physician educators indicated that their association with people including mentors and peers was an essential element for career fulfillment. 9 At the organizational level, connections are seen within organizational units that provide the context in which faculty work and train (e.g., labs, centers, divisions, departments).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2 weeks prior to the focused discussion, participants were given a list of readings to complete that dealt with methodological issues and the concept of units of production in academia; performance criteria for faculty promotion and reward; faculty vitality; and contemporary definitions of scholarship and faculty productivity. 7,10,[13][14][15][16] While regarded as essential to accomplishing the University's mission, service-related activities were not included in the project for 2 reasons. For one, service activities had not previously been studied in similar projects.…”
Section: Identifying Activities/units Of Production (Step 1)mentioning
confidence: 99%
“…These processes are used in combination with other management methods to provide individual recognition and reward as well as to support the promotion and tenure process and to gauge the productivity of the School's Divisions collectively. In response to requests from School faculty members that they gain a better understanding of the activities valued and performed by colleagues, and in response to various internal and external forces demanding greater accountability among faculty members, 6,7 the investigators undertook a project aimed at identifying and weighting scholarly activities among its constituent members.…”
Section: Introductionmentioning
confidence: 99%
“…5 The reasons for such widespread discontent are diverse and include the perceived poor quality of life for faculty members, a lack of recognition for teaching in many medical schools, a lack of opportunities to participate in decisions which affect all faculty members, and a lack of opportunities for faculty development. 6 Turnover of faculty members in medical schools is very high and replacing faculty members is very expensive. Well planned faculty development programs that respond directly to faculty members' needs have been shown to improve satisfaction and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Well planned faculty development programs that respond directly to faculty members' needs have been shown to improve satisfaction and retention. 6,7 Furthermore, the most powerful predictor of productivity for an individual faculty member is his or her institutional environment. 8 Faculty development is an important resource to support productivity.…”
Section: Introductionmentioning
confidence: 99%